Peningkatan Akses Pendidikan dalam rangka mengahadapi Pelaksanaan Wajib Belajar 12 Tahun di Kab. Tanjab Timur Tahun 2008 - Ade Rahima; Erlina Zahar (Universitas Batanghari Jambi, 2011)
This study menkaji about improving access to education and the implementation of the compulsory 9 years in the district.East Tanjab. Samples taken from two sub-district. In the district.East Tanjab. Ditentntukan school sample with random sampling technique. Results obtained dalah: 1) Achieving increased access to education at the primary level is much better than at the level of SMP / MTs. 2) Based on the indicators of GER, NER, school dropout (DO) and number of repeat classes, the district has not met the target East Tanjab reasonable thoroughness 9 years in an optimal fit mandated by the Presidential Instruction No. 5 / 2006 which is unable to maintain NER SD / MI of 95% and education GER SMP / MTs has not reached 95%. It can be concluded that unlicensed although aksess education in the district.East Tajabbeen no improvement but not yet ready to implement the Fair 12 years.